2015
DOI: 10.1111/tbed.12347
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices Related to African Swine Fever Within Smallholder Pig Production in Northern Uganda

Abstract: Uganda is a low-income country with the largest pig population in East Africa. Pig keeping has a large potential, commercially and as a tool for poverty reduction, but African swine fever (ASF) is a major hurdle for development of the sector. The objective of this study was to evaluate knowledge, attitudes and practices related to ASF in the smallholder pig production value chain in northern Uganda. The study included three separate series of participatory rural appraisals (PRA), comprising purposively selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 27 publications
15
102
1
Order By: Relevance
“…Lessons learned from participatory research ( Jacobson, 2013;Calderon, 2013) and from recent social science engagement with PE (Leach and Scoones, 2013;Tschakert et al, 2016;Craddock and Hinchliffe, 2015;Coffin et al, 2015) indicate that this can have a significant impact on the validity and local relevance of PE research results in the future. It could help us see (and ultimately address) how power dynamics with-in local communities, as well as between smallholders and authorities, affect disease impact and control (Craddock and Hinchliffe, 2015), and bring important clarity to the multiple factors influencing human behaviour and habits crucial for disease control, while avoiding over-simplistic explanation models citing "lack of knowledge" as the main cause of continuous disease transmission (Coffin et al, 2015;Chenais et al, 2015b;Tschakert et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Lessons learned from participatory research ( Jacobson, 2013;Calderon, 2013) and from recent social science engagement with PE (Leach and Scoones, 2013;Tschakert et al, 2016;Craddock and Hinchliffe, 2015;Coffin et al, 2015) indicate that this can have a significant impact on the validity and local relevance of PE research results in the future. It could help us see (and ultimately address) how power dynamics with-in local communities, as well as between smallholders and authorities, affect disease impact and control (Craddock and Hinchliffe, 2015), and bring important clarity to the multiple factors influencing human behaviour and habits crucial for disease control, while avoiding over-simplistic explanation models citing "lack of knowledge" as the main cause of continuous disease transmission (Coffin et al, 2015;Chenais et al, 2015b;Tschakert et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, producers are reluctant or unable to invest in improving management by confining their pigs, feeding them on commercial rations and providing basic health care (Lekule & Kyvsgaard, ; Penrith et al., ; Verhulst, ). The risks posed by feeding pigs garbage, either as swill or by releasing them to scavenge, and by selling pigs through agents who move from farm to farm, are compounded by panic selling of pigs and infected pork during outbreaks of ASF, which serves to spread the disease (Brown et al., ; Chenais, Boqvist, Sternbgerg‐Lewerin, et al., ; Dione, Ouma, Opio, Kawuma, & Pezo, ; Dione et al., ; Lichoti et al., ; Muwonge et al., ; Nantima et al., ). A survey of pig sales patterns on the border between Kenya and Uganda revealed that producers selling sick pigs tend to seek markets in communities further away from their usual outlets (Lichoti et al., ).…”
Section: Transmission Routes Of Asfv In Domestic Cyclesmentioning
confidence: 99%
“…The origin of reported outbreaks is frequently unknown but there is sufficient information to build a certain level of understanding of the drivers of ASF maintenance and spread in Africa and the relative importance of African wild suids and domestic pigs in the epidemiology of ASF in Africa today. Studies in resource‐poor pig‐keeping communities in African countries, in particular, have demonstrated that socio‐economic factors are major constraints for control of ASF (Chenais, Boqvist, Emanuelson, et al., ; Chenais, Boqvist, Sternberg‐Lewerin, et al., ). The aim of the study is to provide information useful for future research planning and ASF management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs in infected areas should be confined (instead of held outdoors) in order to prevent them from coming into contact with wild boar or pigs from other farms, as well as to prevent scavenging activities. Control failures may be caused by cultural practices (Mur, Atzeni, et al., ), trade of infected products and the taboo of throwing away food observed in some cultures (Chenais et al., ).…”
Section: Prevention Detection and Controlmentioning
confidence: 99%